VD_FINDINFO 391 vom 20. März 2023 - VD Tribunal cantonal (2023)
VOIES DE FAIT, SÉJOUR ILLÉGAL, FRONTALIER, CONCUBINAGE, INDEMNITÉEN GÉNÉRAL, DÉFENSE D'OFFICE | 126 al. 2 CP, 40 CP, 41 CP, 135 CPP (CH), 115 al. 1 let. b LEI